Un modèle indien du développement des TIC ? - Clarisse Didelon; Blandine Ripert (Netcom)
During the last years, the image of India in the western media is becoming better with a focus on the Indian informatics engineers very well connected in the information society. However, the diffusion of information and communication technologies in India does not follow a specific model that would allow to the larger part of the population and more especially the poorest ones to access to it. The diffusion model is very similar to what is observed elsewhere both in developed or developing countries. More, the projects set up, mainly located in the countryside, meet numerous obstacles.